Proliferative Effect of Aqueous Extracts ofParquetina Nigrescens on HaemopoieticMultipotent Stem Cells in Irradiated Guinea Pigs - LO Olatunbosun, A Caxton-Martin, OR Jimoh, SA Biliaminu, OK Ghazal (Journal of Applied Pharmaceutical Science)
Patients suffer a decrease in haemopoietic stem cells as a consequence of disease, radiation or chemotherapy. Radiotherapy and chemotherapy are common therapeutic modalities for cancer, leukemia, and lymphoma. Unfortunately, these therapies are not tumor-specific. Normal tissues, particularly the bone marrow (BM), are extremely vulnerable to cytotoxicity caused by these therapies. Antidotes are required for the untoward side effects of these therapies. Although a lot of potential better treatments are currently being developed, few research studies have investigated the proliferative effect of plant extracts which may modulate stem cells self-renewal and differentiation. However, in recent years there has been an upsurge of interest on the effects of various dietary insufficiencies on haemopoietic and immune responses (Sanberg et al., 2006). Other investigators have recently reported that dietary fatty acids, particularly oleic acid and linoleic acid, actively promote the proliferation of haemopoietic stem cells (Sanberg et al., 2006) as well as modulate the self-renewal of intestinal epithelial cells. This study was done to determine the potential proliferative effect of Parquetina nigrescens on haemopoietic multipotent stem cells in irradiated guinea pigs bone marrow. The study shows that the plant has positive proliferative effects on haemopoietic multipotent stem cells. The proliferative effect correlates with the concentration of the P. nigrescens.
Keywords: Proliferative effect,Parquetina nigrescens,Haemopoietic,Multipotent Stem Cells,Irradiated Guinea Pigs.